2019
DOI: 10.1101/588608
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic and phylogenetic analysis ofSalmonellaTyphimurium and its monophasic variants responsible for invasive endemic infections in Colombia

Abstract: Salmonellosis is an endemic human infection, associated with both sporadic cases and outbreaks throughout Colombia. Typhimurium is the most common Colombian serovar of Salmonella enterica, responsible for 32.5% of the Salmonella infections. Whole genome sequencing (WGS) is being used increasingly in Europe and the USA to study the epidemiology of Salmonella, but there has not yet been a WGS-based analysis of Salmonella associated with bloodstream infection in Colombia. Here, we analysed 209 genome sequences of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 56 publications
2
10
0
3
Order By: Relevance
“…Regarding the integrons located in SGI-1 variants, the result are agree with that in Colombia circulated the pandemic S. Typhimurium MDR DT104 (Li et al, 2019), but with variations during the time. Surveillance of isolates associated with the S. Typhimurium MDR DT104 pandemic showed the same MDR signature of this phage type, which were also identified within the global time line in which it appeared and spread throughout the world (Leekitcharoenphon et al, 2016).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Regarding the integrons located in SGI-1 variants, the result are agree with that in Colombia circulated the pandemic S. Typhimurium MDR DT104 (Li et al, 2019), but with variations during the time. Surveillance of isolates associated with the S. Typhimurium MDR DT104 pandemic showed the same MDR signature of this phage type, which were also identified within the global time line in which it appeared and spread throughout the world (Leekitcharoenphon et al, 2016).…”
Section: Discussionsupporting
confidence: 86%
“…Regarding clonality, the 30 S. Typhimurium isolates belong to worldwide spread ST19 that circulates in Colombia (Li et al, 2019) and the SNP phylogenetic analysis suggests that the different mobile elements identified in this study affect the subpopulations lineages. We observed that the 11 S. Typhimurium isolates bearing IntI1-Col1 belong to a subclonal lineage (Figure 5A), whereas the isolates with SGI-1 grouped in another branch (Figure 5B).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Furthermore, S. Paratyphi B was the second most frequently isolated serotype among all Salmonella isolates, and were distributed throughout the different processing sites. Previously published work reported that S. Paratyphi B dT+ and S. Heidelberg were the most prevalent serotypes isolated from farms and retail meat samples in Colombia during 2008 and 2009 [28]. There were also three S. Typhimurium ST19 strains isolated from plant B with a high abundance of AMR genes.…”
Section: Discussionmentioning
confidence: 92%
“…isolates recovered from retailed chicken carcasses in Bogota. Another study conducted by the same group [28] reported the AMR profiles of 378 Salmonella spp. isolates from chicken carcasses available in wet markets, supermarkets, and independent markets, collected in six different Departments.…”
Section: Discussionmentioning
confidence: 99%